PEMBUATAN ALAT MUSIK TRADISIONAL SAPE DI DESA DEDAI KANAN KABUPATEN SINTANG KALIMANTAN BARAT - Rusdi, Rusdi; Wibowo, Dwi Cahyadi (JPPM: Jurnal Pelayanan dan Pemberdayaan Masyarakat, 2023)
This Pkm activity has the aim of providing a solution to lovers of traditional sape musical instruments, namely by making traditional Dayak musical instruments where the Sape musical instrument is an original Indonesian art product. This PkM activity also aims to foster the creativity of youth and traditional music lovers, as well as to maintain the artistic values of music in today's society. It is hoped that this product can foster enthusiasm for youth and village youth and the community to love the traditional values possessed by the Dayak tribe and to be able to innovate and be entrepreneurial in the products they produce. the implementation we started with the planning of product manufacture, namely the collection of materials. Then we made observations of market conditions and needs.Then make a prototype first and do a feasibility test on the product. After the product was deemed suitable, we produced it and studied the sape making process. After the product is finished, then do the finishing to beautify the product. The next stage describes the process of selecting wood raw materials, both selecting the shape of the sape and the shape you want to make. The three finishing considerations are made for selecting the concept and theme to match what you want to create.Keywords: Sape Traditional Musical Instruments, Sape Making Process